Carbon ceramic composite conductive microsphere, ceramic resistor and preparation method
By using impregnation method and buried carbon sintering process in the ceramic matrix, carbon ceramic composite conductive microspheres are formed, which solves the problem of uneven dispersion of carbon materials in the ceramic matrix, and achieves the efficient conductivity and mechanical properties of ceramic resistance.
Patent Information
- Application Number
- CN202510105057.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to disperse carbon materials evenly in ceramic matrix, resulting in discontinuity of conductive paths and reducing the electrical and mechanical properties of carbon/ceramic composite conductive materials.
The precursor solution of carbon and the carbon-containing black slurry were impregnated into porous mullite by impregnating the carbon ceramic composite conductive microspheres by drying and buried carbon sintering processes, which were combined with the ceramic raw materials as conductive fillers to form a continuous conductive path.
The dispersion and uniformity of carbon materials in the ceramic matrix are improved, and a continuous conductive path is formed, which significantly improves the electrical and mechanical properties of the ceramic resistor, meeting the needs of ultra-high voltage circuit breaker closing resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special material production for electrical equipment, and specifically relates to a carbon ceramic composite conductive microsphere and a ceramic resistor and a preparation method thereof. Background Art
[0002] With the widespread development of electric energy utilization, ultra-high voltage transmission lines, as an important part of the power grid system, have shown significant social and economic benefits due to their advantages such as large transmission capacity and long transmission distance. Ultra-high voltage circuit breakers, as key equipment in power transmission and distribution systems, mainly play the role of breaking current in power systems. When a system fault occurs, the circuit breaker and relay protection can cooperate to quickly cut off the fault current to prevent the scope of the accident from expanding. Therefore, the stability and reliability of the circuit breaker directly affect the safe operation of the power system. As an important part of the ultra-high voltage circuit breaker, the closing resistor can limit the closing inrush current during the opening and closing process of the circuit breaker and protect the normal operation of the transmission system.
[0003] The manufacturing process of closing resistors is complex and technically difficult, and they are still dependent on imports, which has increasingly highlighted the constraints on the localization of ultra-high voltage transmission systems. Carbon / ceramic composite conductive materials prepared with carbon materials as conductive fillers have many advantages such as low preparation cost, simple process, industrial production, adjustable resistivity, corrosion resistance, and high temperature resistance. They have shown great application potential in the field of ultra-high voltage circuit breaker closing resistors and have been widely studied. However, carbon materials are easy to agglomerate and disperse unevenly in the ceramic matrix, which will affect the formation of the conductive path inside the material, reduce the electrical properties of the material, and deteriorate the mechanical properties of the material.
[0004] Therefore, it is necessary to find a new preparation method to improve the dispersion of carbon materials in the ceramic matrix and reduce the agglomeration of carbon materials, so that the carbon / ceramic composite conductive materials can synergistically improve the electrical and mechanical properties, better serve as closing resistors for circuit breakers, and break the monopoly situation. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a carbon-ceramic composite conductive microsphere and a ceramic resistor and a preparation method, so as to solve the technical problem of how to improve the dispersibility of carbon materials in the ceramic matrix and reduce agglomeration, thereby improving the electrical and mechanical properties of the ceramic resistor and meeting the closing resistance requirements of ultra-high voltage circuit breakers.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing carbon ceramic composite conductive microspheres, comprising: The ceramic phase matrix is firstly impregnated in a carbon precursor solution, then impregnated in a carbon black slurry for a second time, and then dried and carbon-embedded and sintered in sequence to obtain carbon-ceramic composite conductive microspheres; The carbon precursor solution is prepared by adding ammonium cobalt acetate to a tartaric acid solution and mixing them for reaction; The carbon black slurry is prepared by adding octylphenol polyoxyethylene ether to a carbon black solution and stirring the mixture for reaction; The ceramic phase matrix is porous mullite.
[0007] Preferably, the mass percentages of ammonium cobalt acetate, tartaric acid solution, octylphenol polyoxyethylene ether, carbon black solution and porous mullite are (1%-2%): (50%-60%): (1%-2%): (15%-20%): (20%-35%); ensuring the optimal distribution and interaction of each component in the composite material. Ammonium cobalt acetate is used as a catalyst, and its appropriate addition can effectively catalyze the pyrolysis and carbonization of tartaric acid solution to generate a carbon material with catalytic activity. Tartaric acid solution is used as the main carbon source, and its proportion ensures sufficient carbon material generation. Octylphenol polyoxyethylene ether is used as a surfactant, and its appropriate presence helps to uniformly disperse carbon black. The addition of carbon black solution improves the conductive properties. The apparent porosity of porous mullite is 30%-60%. The high apparent porosity of porous mullite provides sufficient pore structure, which is convenient for the penetration and attachment of carbon materials, and its own conductivity also enhances the conductive network of the composite material.
[0008] Preferably, the temperature of the first impregnation is 40-60 ° C, and the time of the first impregnation is 1-4 h; the temperature of the second impregnation is 40-60 ° C, and the time of the second impregnation is 1-4 h; the first impregnation and the second impregnation are both carried out in a vacuum environment, and the pressure is maintained at -0.098 MPa; the appropriate impregnation temperature and time ensure that the carbon precursor solution and the carbon black slurry can fully penetrate into the pores of the porous mullite, and the vacuum environment helps to remove the air in the pores, improve the impregnation effect, and make the carbon material more evenly dispersed in the ceramic phase matrix.
[0009] The conditions for the mixing reaction are: mixing reaction at a speed of 1100-1350 r / min and at 30-60°C for 40-100 min; the conditions for the stirring reaction are: stirring reaction at a speed of 1100-1350 r / min and at 30-60°C for 40-100 min; the specific mixing reaction and stirring reaction conditions ensure the full mixing and uniform dispersion of the components, avoid the agglomeration of carbon black particles, improve the dispersion and uniformity of the carbon material in the ceramic phase matrix, and are conducive to the formation of a continuous conductive path.
[0010] The drying temperature is 60-100 °C and the drying time is 18-36 h. Appropriate drying temperature and time can completely remove excess moisture and solvent in the composite material, avoid the generation of pores or cracks in the subsequent sintering process, and improve the density and mechanical properties of the composite material.
[0011] Preferably, the temperature of carbon embedding sintering is 800-1000℃, and the holding time of carbon embedding sintering is 3-5 hours; the carbon embedding sintering process promotes the conversion of carbon precursor solution and carbon black slurry into a variety of in-situ carbon materials at high temperature, and improves the antioxidant and mechanical properties of the composite material. Appropriate sintering temperature and holding time ensure good bonding between the carbon material and the ceramic phase matrix, forming a stable conductive path.
[0012] The invention discloses a carbon-ceramic composite conductive microsphere, which is prepared by the above-mentioned carbon-ceramic composite conductive microsphere preparation method. The carbon-ceramic composite conductive microsphere comprises ceramic phase porous mullite and conductive phase carbon contained in the ceramic phase porous mullite. The diameter of the carbon-ceramic composite conductive microsphere is 80-90 μm.
[0013] The invention discloses a method for preparing a ceramic resistor, comprising the following steps: The slurry composed of the conductive filler and the binder is impregnated in the mud composed of the ceramic raw material and the surfactant by vacuum-assisted centrifugal impregnation, and then dried and debinded, isostatically pressed and sintered by gas pressure are performed in sequence, cooled to room temperature, and then mechanically treated and sprayed with electrodes to obtain a ceramic resistor; The conductive filler is a carbon ceramic composite conductive microsphere prepared by the preparation method of the carbon ceramic composite conductive microsphere.
[0014] Preferably, the mass percentages of the conductive filler, binder, ceramic raw material and surfactant are (5%-9%): (0.5%-1.5%): 1: (0.5%-1.5%); The conductive filler plays a key role in transmitting current. Its mass percentage is controlled at 5%-9%, which can not only ensure that the material has good conductivity, but also avoid excessive filler content causing material processing difficulties or decreased mechanical properties. The binder is used to bind the components together tightly to form a stable composite material structure. Its mass percentage is 0.5%-1.5%, which can not only ensure good bonding between the components, but also avoid excessive binder causing material performance degradation. The surfactant is used to improve the compatibility and dispersibility between the components, improve the processing performance of the material and the uniformity of the final product, and its mass percentage is also controlled at 0.5%-1.5% to ensure that the best dispersion and compatibility effects are achieved without affecting the material performance too much.
[0015] In terms of mass percentage, the ceramic raw materials include 63%-67% bauxite, 6%-8% silicon micropowder, 17%-19% kaolin and 8%-12% raw clay; bauxite, as the main component of ceramic raw materials, has high refractoriness and good mechanical properties, and its mass percentage is controlled at 63%-67%, providing stable basic performance for composite materials. The addition of silicon micropowder can improve the hardness and wear resistance of the material, and at the same time help to improve the sintering performance of the material. Its mass percentage is 6%-8%, which not only ensures the performance improvement of the material, but also avoids the difficulty of material processing caused by excessive silicon micropowder. Kaolin has good plasticity and adhesion, which helps to improve the molding performance and sintering density of the material. Its mass percentage is controlled at 17%-19%, providing good processing performance for the preparation of composite materials. The addition of raw clay can further improve the plasticity and adhesion of the material, and at the same time help to adjust the sintering speed and temperature of the material. Its mass percentage is 8%-12%, providing more flexibility and controllability for the preparation of composite materials.
[0016] The binder is polyvinyl alcohol; it has good bonding and film-forming properties and can effectively bind the components tightly together to form a stable composite material structure.
[0017] The surfactant is lecithin, which has good biocompatibility and dispersibility, and can effectively improve the compatibility and dispersibility between the components, improve the processing performance of the material and the uniformity of the final product. At the same time, the addition of lecithin also helps to improve the wettability and fluidity of the material, further improving the processing performance of the material.
[0018] Preferably, the vacuum degree of the vacuum-assisted centrifugal impregnation method is maintained at 0.3 atm, the rotation speed is 300-600 rpm, and the impregnation time is 2-6 h; the control of the vacuum degree is crucial to the impregnation process. The vacuum degree of 0.3 atm can provide a moderate negative pressure environment, which helps the impregnation liquid to penetrate into the impregnated material more evenly, while avoiding the destruction of the material structure or excessive volatilization of the impregnation liquid caused by too high a vacuum degree. The choice of centrifugal speed directly affects the penetration speed and effect of the impregnation liquid. The speed of 300-600 rpm can not only ensure that the impregnation liquid has enough power to overcome the resistance inside the material and penetrate deeply into the material, but also avoid material damage or splashing of the impregnation liquid caused by too high a speed. The setting of the impregnation time needs to comprehensively consider factors such as the viscosity of the impregnation liquid, the pore structure of the material, and the penetration depth. The impregnation time of 2-6 h can not only ensure that the impregnation liquid fully penetrates into the material, but also avoid changes in material properties or waste of impregnation liquid caused by too long an impregnation time.
[0019] The drying temperature is 60-100 ℃; the drying time is 18-36 h. The selection of drying temperature needs to take into account factors such as the thermal stability of the material, the volatility of the impregnation liquid, and the drying efficiency. Within this temperature range, the impregnation liquid can be quickly and completely volatilized, while avoiding thermal damage or performance changes of the material caused by excessive temperature. The setting of the drying time needs to ensure that the moisture or impregnation liquid inside the material is completely volatilized, while avoiding material aging or performance degradation caused by too long drying time. A drying time of 18-36 h can not only meet this requirement, but also improve production efficiency.
[0020] Preferably, the pressure of the isostatic pressing is 200-300 MPa. Within this pressure range, the material can be fully compacted to achieve the required density and strength, while material rupture or performance degradation caused by excessive pressure can be avoided.
[0021] The sintering temperature of gas pressure sintering is 1300-1400 ℃, and the holding time is 2-4 h. Within this temperature range, the material can undergo sufficient solid-phase reaction to form a dense sintered body, while avoiding overheating or performance deterioration of the material caused by excessively high temperature. The setting of the holding time needs to ensure that the material has sufficient reaction time during the sintering process to achieve the required phase composition and microstructure. A holding time of 2-4 h can not only meet this requirement, but also improve production efficiency. Gas pressure sintering can achieve rapid densification of materials at higher temperatures and pressures, significantly improve the mechanical properties, thermal stability and corrosion resistance of the materials, and provide a broad space for the application of materials.
[0022] The ceramic resistor disclosed in the present invention is prepared by the above-mentioned preparation method of the ceramic resistor, and the volume density of the ceramic resistor is ≥2.25 g / cm 3 .
[0023] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing carbon ceramic composite conductive microspheres. First, a carbon precursor solution and a carbon black slurry are successively impregnated into porous mullite by an impregnation method, thereby promoting the carbon precursor solution to better penetrate into the carrier pore structure of the porous mullite, and ensuring that the porous mullite is wrapped by the carbon black slurry, which helps to improve the dispersion and uniformity of the carbon material in the ceramic phase matrix, thereby facilitating the formation of a continuous conductive path, and the direct introduction of carbon black also improves the conductive performance of the conductive filler. After drying treatment and carbon embedding sintering process treatment, carbon ceramic composite conductive microspheres are prepared. The drying treatment removes excess water and solvent, and the carbon embedding sintering process promotes the conversion of the carbon precursor solution and the carbon black slurry into a variety of in-situ carbon materials, and improves the antioxidant performance of the composite material, promotes the bonding between the carbon and ceramic interface, and thus improves the mechanical properties and electrical properties of the ceramic resistor. Tartaric acid solution is used as a precursor solution, carbon black solution is used as an additional carbon source, ammonium cobalt acetate is used as a catalyst, octylphenol polyoxyethylene ether is used as a surfactant, and porous mullite is used as a ceramic phase matrix. Ammonium cobalt acetate is used as a catalyst to catalyze the thermal decomposition and carbonization process of the tartaric acid solution, thereby generating a carbon material with catalytic activity. This carbon material can better combine with the ceramic phase matrix in the subsequent sintering process to form a stable conductive path. Octylphenol polyoxyethylene ether is used as a surfactant to effectively disperse the carbon black particles in the carbon black solution and prevent them from agglomerating. This helps to evenly distribute the carbon black in the ceramic phase matrix, thereby improving the conductive properties of the conductive filler. Porous mullite has good pore structure and thermal stability, and can accommodate a large amount of carbon material and provide attachment points for it. At the same time, porous mullite itself also has a certain conductivity, and can form a more complete conductive network after combining with carbon material, thereby improving the conductive properties of the ceramic resistor made of carbon ceramic composite conductive microspheres. The preparation method of carbon ceramic composite conductive microspheres disclosed in the present invention not only simplifies the experimental process, but also improves the dispersion and uniformity of carbon materials in the ceramic phase matrix, reduces the agglomeration of carbon materials, and is conducive to the formation of a continuous conductive path. At the same time, the application of the carbon buried sintering process also improves the antioxidant properties and mechanical properties of the composite material, so that the prepared ceramic resistor can synergistically control the mechanical properties and electrical properties.
[0024] The present invention also discloses a carbon ceramic composite conductive microsphere, which is prepared by the above-mentioned preparation method. The carbon material in the carbon ceramic composite conductive microsphere is evenly distributed in the ceramic phase matrix to form a continuous conductive path. The carbon material includes carbon converted from a carbon precursor solution and carbon black directly introduced, which enriches the types of carbon materials. The diverse carbon materials form a more complex conductive network in the ceramic phase matrix, further improving the conductivity and stability of the ceramic resistor. This structure makes the transmission of electrons in the ceramic resistor smoother, thereby significantly improving the conductivity of the ceramic resistor. The carbon material forms a stable structure in the ceramic matrix, which helps to resist the corrosion of the ceramic resistor by oxidation, and can maintain stable conductivity and mechanical properties under high temperature or harsh environment. When the carbon ceramic composite conductive microsphere is used in the preparation of closing resistors for ultra-high voltage transmission lines, the ultra-high voltage transmission lines require the closing resistors to have extremely high conductivity and withstand voltage. The carbon material in the carbon-ceramic composite conductive microspheres provides a good conductive path, while the ceramic matrix has a high voltage resistance. The resulting closing resistor for ultra-high voltage transmission lines can work stably in ultra-high voltage environments, ensuring efficient current transmission while resisting potential damage caused by high voltage. In ultra-high voltage transmission lines, the closing resistor may generate a lot of heat due to excessive current. Carbon-ceramic composite conductive microspheres, which combine the high thermal stability of ceramics and the thermal conductivity of carbon materials, can effectively disperse and withstand this heat, preventing the resistor from being damaged due to overheating, thereby improving the safety and reliability of the system. Ultra-high voltage transmission lines are often exposed to harsh natural environments, such as high temperature, humidity, salt spray, etc. Carbon-ceramic composite conductive microspheres have good oxidation resistance and corrosion resistance, can resist the erosion of these environmental factors, and extend the service life of the closing resistor.
[0025] The present invention also discloses a method for preparing a ceramic resistor, and the carbon ceramic composite conductive microspheres prepared by the above preparation method are used as conductive fillers, which can synergistically control the mechanical properties and electrical properties. The conventional method for preparing ceramic resistors is to directly mix the carbon material with the ceramic raw material, and then shape it through mechanical forming technology and sinter it. However, this method has a big problem. Since the conductive filler is difficult to disperse evenly and not agglomerate in the ceramic phase matrix, the ceramic resistivity is large and unstable. The carbon ceramic composite conductive microspheres prepared by the above preparation method of the present invention are used as conductive fillers, which can form a continuous conductive path in the ceramic phase matrix, and synergistically improve the mechanical properties and electrical properties of the ceramic resistor.
[0026] The present invention also discloses a ceramic resistor, which is prepared by the above-mentioned preparation method. The carbon material forms a continuous conductive path inside the ceramic phase matrix, and the carbon material itself has good conductivity, so the prepared ceramic resistor has excellent conductive properties. This high-performance conductivity enables the ceramic resistor to transmit current more efficiently in electrical equipment and reduce energy consumption. A strong interface bond is formed between the carbon material and the ceramic matrix in the carbon-ceramic composite conductive microspheres, and this bond enhances the overall structural stability of the ceramic resistor. Therefore, the prepared ceramic resistor has higher mechanical strength and impact resistance, and can maintain its integrity and performance in harsh environments. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] It should be noted that the terms “include” and “have” and any variations thereof in the specification and claims of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units that are not explicitly listed or are inherent to these processes, methods, products or apparatuses.
[0029] The present invention is described in further detail below: The present invention discloses a method for preparing carbon ceramic composite conductive microspheres, comprising the following steps: S1. By mass percentage, weigh 1%-2% of the catalyst ammonium cobalt acetate and place it in a 50%-60% tartaric acid solution and heat it on a water bath magnetic stirrer at a speed of 1100-1350 r / min at 30-60 ° C for 40-100 minutes until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0030] S2. In terms of mass percentage, 1%-2% of the surfactant octylphenol polyoxyethylene ether is weighed and placed in a 15%-20% carbon black solution, and stirred on a magnetic stirrer at a speed of 1100-1350 r / min and at 30-60 °C for 40-100 min to obtain a carbon black slurry; the carbon black solution is prepared by uniformly mixing carbon black powder and deionized water in a mass ratio of 1:1.
[0031] S3. In terms of mass percentage, place 20%-35% porous mullite in a vacuum barrel, turn on the vacuum pump to remove the gas in the barrel, and when the pressure indication is stable at -0.098 MPa, slowly open the valve switch connected to the precursor solution, first completely inject the carbon precursor solution into the vacuum barrel, close the valve switch, perform a primary impregnation, and keep the impregnation at 40-60 ℃ for 1-4 hours; then inject the carbon black slurry for a secondary impregnation, and continue to keep the impregnation at 40-60 ℃ for 1-4 hours. Ensure that the porous mullite is fully infiltrated, turn off the vacuum pump after the impregnation, and take out the sample.
[0032] S4. Place the impregnated porous mullite in an electric hot air dryer at 60-100°C for 18-36 hours until it is completely dry.
[0033] S5. The porous mullite powder after impregnation and drying is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, which is then buried in a corundum-mullite crucible. Coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800-1000℃ for 3-5 h for carbon sintering to ensure that the tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is taken out after cooling to room temperature with the furnace to obtain carbon-ceramic composite conductive microspheres.
[0034] The present invention discloses a method for preparing a ceramic resistor, comprising the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0035] S6. In terms of mass percentage, 1 part of ceramic raw material, 5%-9% of conductive filler carbon ceramic composite conductive microspheres, 0.5%-1.5% of binder polyvinyl alcohol, and 0.5%-1.5% of surfactant lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 63%-67% of bauxite, 6%-8% of silicon micropowder, 17%-19% of kaolin and 8%-12% of raw clay. The slurry consisting of the conductive filler and the binder is impregnated into the mud consisting of the ceramic raw material and the surfactant by vacuum-assisted centrifugal impregnation in a manipulator single-cylinder impregnation and spinning coating machine. The vacuum degree of the vacuum-assisted centrifugal impregnation is maintained at 0.3 atm, the rotation speed is 300-600 rpm, the impregnation time is 2-6 h, and the ceramic slurry is obtained by mixing.
[0036] S7. Place the ceramic slurry in a 60-100 °C oven and dry it for 18-36 h to completely dry and remove binder. Then, perform isostatic pressing at 200-300 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0037] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1300-1400 °C for 2-4 h. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0038] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0039] The ceramic resistor disclosed in the present invention uses carbon ceramic composite conductive microspheres as conductive fillers, and the volume density of the prepared ceramic resistor is ≥2.25 g / cm 3 .
[0040] The present invention discloses a carbon ceramic composite conductive microsphere, which comprises, by mass percentage, 50%-60% tartaric acid solution as a carbon precursor, 15%-20% carbon black solution as nanocarbon, 20%-35% porous mullite as a ceramic phase matrix, 1%-2% ammonium cobalt acetate as a catalyst, and 1%-2% octylphenol polyoxyethylene ether as a catalyst, and obtains the carbon ceramic composite conductive microsphere after impregnation, drying, and sintering. The porous mullite has an apparent porosity of 30%-60%. The impregnation method is vacuum-assisted impregnation, wherein the porous mullite is placed in a vacuum barrel, and the tartaric acid precursor solution and the carbon black slurry are sequentially injected into the vacuum barrel at 40-60°C, and the impregnation is maintained for 1-4 hours respectively. The prepared carbon ceramic composite conductive microsphere is composed of conductive phase carbon and ceramic phase porous mullite, and the diameter of the carbon ceramic composite conductive microsphere is 80-90 μm.
[0041] The invention discloses a ceramic resistor. The raw materials include, by mass percentage, 1 part of conductive filler and 63%-67% of bauxite, 6%-8% of silicon powder, 17%-19% of kaolin, 8%-12% of raw clay, 0.5%-1.5% of binder polyvinyl alcohol (PVA) and 0.5%-1.5% of surfactant lecithin. The ceramic resistor is obtained by vacuum-assisted centrifugal impregnation, drying, isostatic pressing, gas pressure sintering, mechanical treatment, and spraying of silver electrodes.
[0042] The present invention uses an impregnation method to make the carbon precursor solution and the carbon black slurry successively impregnate the porous mullite, thereby promoting the carbon precursor solution to better penetrate into the carrier pore structure of the porous mullite, and ensuring that the porous mullite is wrapped by the carbon black slurry containing nano carbon black. After drying treatment and carbon burying sintering process, the carbon precursor solution and the carbon black slurry are converted into a variety of in-situ carbon materials to obtain carbon ceramic composite conductive microspheres. Then, the carbon ceramic composite conductive microspheres are used as conductive fillers and are combined with ceramic raw materials, binder polyvinyl alcohol and surfactant lecithin through vacuum-assisted centrifugal impregnation, primary isostatic pressing, and gas pressure sintering processes to finally obtain ceramic resistors. The volume density of the prepared ceramic resistor is ≥2.25 g / cm 3 .
[0043] The present invention uses carbon ceramic composite conductive microspheres prepared by the impregnation method as conductive fillers, which not only simplifies the experimental process, but more importantly, improves the dispersion and uniformity of carbon materials in the ceramic phase matrix, reduces the agglomeration of carbon materials, and is conducive to the formation of a continuous conductive path of carbon materials inside the ceramic phase matrix, thereby improving the electrical properties of ceramic resistors. In addition, the introduction of nano carbon black in the carbon black slurry also enriches the types of carbon materials. The application of the carbon-embedded sintering process improves the antioxidant properties of ceramic resistors, promotes the bonding between the carbon and ceramic interfaces, ensures the overall structural stability of ceramic resistors, and improves the mechanical properties of ceramic resistors, thereby better serving as closing resistors for circuit breakers.
[0044] The conventional method for preparing ceramic resistors is to directly mix carbon materials with ceramic raw materials, and then shape them through mechanical molding technology and sinter them. However, this method has a big problem. Since the conductive filler is difficult to disperse evenly in the ceramic matrix and is easy to agglomerate, the ceramic resistivity is large and unstable. The present invention obtains carbon ceramic composite conductive microspheres by impregnating a carbon precursor solution and a carbon black slurry into a ceramic phase matrix, and then performs carbon embedding sintering. The carbon ceramic composite conductive microspheres are used as conductive fillers to form a continuous conductive path in the ceramic phase matrix, thereby synergistically improving the mechanical and electrical properties of the ceramic resistor. Tartaric acid solution, ammonium cobalt acetate, carbon black solution, octylphenol polyoxyethylene ether, porous mullite, bauxite, silicon powder, kaolin, raw clay, polyvinyl alcohol and lecithin are used as raw materials, tartaric acid solution is used as a precursor solution, carbon black solution is used as a carbon source, ammonium cobalt acetate is used as a catalyst, octylphenol polyoxyethylene ether is used as a surfactant, porous mullite is used as a ceramic phase matrix, carbon ceramic composite conductive microspheres prepared by an impregnation method and a carbon-buried sintering process are used as conductive fillers, and vacuum-assisted centrifugal impregnation, drying, primary isostatic pressing, gas pressure sintering treatment, mechanical treatment, and spraying silver electrodes are used to finally obtain a ceramic resistor with carbon ceramic composite conductive microspheres as conductive fillers. In the ceramic resistor prepared by the present invention, carbon materials are fully and evenly dispersed in the ceramic phase matrix, so that the prepared ceramic resistor can synergistically control mechanical properties and electrical properties.
[0045] Under the raw material ratio given in the present invention, a ceramic resistor with carbon ceramic composite conductive microspheres as conductive filler is prepared in combination with an impregnation process and a carbon-embedded sintering process. The prepared ceramic resistor has excellent performance when used as a closing resistor for ultra-high voltage transmission line breakers.
[0046] The experimental methods in the following examples are conventional experimental methods unless otherwise specified; the materials used in the examples are purchased from conventional chemical reagent companies unless otherwise specified.
[0047] The carbon ceramic composite conductive microsphere disclosed in the present invention is used as a conductive filler, with tartaric acid solution as a precursor solution, carbon black solution as an added carbon source, ammonium cobalt acetate as a catalyst, octylphenol polyoxyethylene ether as a surfactant, and porous mullite as a ceramic phase matrix. First, the carbon precursor solution and the carbon black slurry are impregnated into the porous mullite in sequence by an impregnation method, so as to promote the carbon precursor solution to better penetrate into the porous mullite carrier pore structure, and ensure that the porous mullite is wrapped by the carbon black slurry. The carbon ceramic composite conductive microsphere is prepared by drying treatment and carbon burying sintering in sequence. Subsequently, the prepared carbon ceramic composite conductive microsphere is mixed with ceramic raw materials (bauxite, silicon powder, kaolin and raw clay), binder polyvinyl alcohol, and surfactant lecithin through vacuum-assisted centrifugal impregnation, isostatic pressing, and gas pressure sintering process, and finally a ceramic resistor with carbon ceramic composite conductive microsphere as a conductive filler is obtained. The impregnation process helps the carbon precursor solution and the carbon black slurry to contact each other in the porous mullite ceramic phase matrix, which is beneficial to the further dispersion of a variety of carbon materials in the ceramic raw materials and the formation of conductive pathways, thereby improving the conductivity of the ceramic resistor; at the same time, the use of the carbon-buried sintering process can improve the oxidation resistance of the ceramic resistor, promote the bonding between the carbon and ceramic interfaces, and improve the mechanical properties of the ceramic resistor, so that the prepared carbon-ceramic composite conductive microspheres as conductive fillers The ceramic resistor can synergistically control the mechanical properties and electrical properties.
[0048] In the following examples, a tartaric acid solution prepared from tartaric acid (purity ≥ 99.0%) is used as a precursor of a carbon source, a carbon black solution prepared from nano carbon black (300-700 nm) is used as a direct carbon source, ammonium cobalt acetate (purity ≥ 99.0%) is used as a catalyst, octylphenol polyoxyethylene ether (purity ≥ 99.0%) and lecithin (purity ≥ 99.0%) are used as surfactants, porous mullite (200 mesh) is used as a ceramic phase matrix, bauxite (100 mesh), kaolin (100 mesh), raw clay (100 mesh) and silicon powder (200 mesh) are used as ceramic raw materials, and polyvinyl alcohol (purity ≥ 99.0%) is used as a binder; the above purities all refer to mass percentages.
[0049] Example 1 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 2% of ammonium cobalt acetate by mass percentage and place it in 60% tartaric acid solution, and mix and react at 60 ° C for 100 min at a speed of 1350 r / min on a water bath heating magnetic stirrer until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0050] S2. Weigh 2% of octylphenol polyoxyethylene ether by mass percentage and place it in 20% of carbon black solution, and stir the mixture at 60 °C for 100 min at a speed of 1350 r / min on a water bath heating magnetic stirrer until it is evenly stirred to obtain a carbon black slurry.
[0051] S3. By mass percentage, 35% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 60%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 60°C for 4 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 60°C for 4 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0052] S4. Place the impregnated porous mullite in an electric hot air dryer at 60°C for 36 hours until it is completely dry.
[0053] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 83 μm are obtained.
[0054] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0055] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1.5% of polyvinyl alcohol and 1.5% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 64% of bauxite, 8% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0056] S7. Place the ceramic slurry in an oven at 80 °C and dry it for 30 h to completely dry and remove binder. Then, perform isostatic pressing at 300 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0057] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1400°C for 4 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0058] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0059] The ceramic resistor prepared in Example 1 has the following performance indicators after sampling inspection: volume density is 2.35 g / cm 3 , compressive strength is 242 MPa, resistance value is 4.78 Ω, temperature resistance coefficient is -0.043% / ℃, voltage coefficient is -1.66%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors, that is, volume density ≥2.25 g / cm 3 , compressive strength ≥120 MPa, resistance value 5±0.25 Ω, temperature resistance coefficient -0.05~0.1% / ℃, voltage coefficient -7.5~-0.5% cm / kV.
[0060] It should be noted that the bulk density is tested by the weighing method in accordance with GB / T 25995~2010, and the compressive strength is tested by the pressure test in accordance with GB / T 8489~2006.
[0061] Example 2 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1% of ammonium cobalt acetate by mass and place it in 50% tartaric acid solution, and mix and react it at 30 °C on a water bath heating magnetic stirrer at a speed of 1100 r / min for 40 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0062] S2. In terms of mass percentage, 1% of octylphenol polyoxyethylene ether was weighed and placed in a 15% carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1100 r / min at 30 °C for 40 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0063] S3. By mass percentage, place 20% of porous mullite in a vacuum barrel, and the apparent porosity of the porous mullite is 30%. Turn on the vacuum pump to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, slowly open the valve switch on the side connected to the precursor solution, first completely inject the carbon precursor solution into the vacuum barrel, close the valve switch, and perform a primary impregnation, and keep the impregnation at 40°C for 1 hour; then inject the carbon black slurry for a secondary impregnation, and continue to keep the impregnation at 40°C for 1 hour. Ensure that the porous mullite is fully infiltrated, turn off the vacuum pump after the impregnation, and take out the sample.
[0064] S4. Place the impregnated porous mullite in an electric hot air dryer at 100°C for 18 hours until it is completely dry.
[0065] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 83 μm are obtained.
[0066] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0067] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1.5% of polyvinyl alcohol and 1.5% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 64% of bauxite, 8% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0068] S7. Place the ceramic slurry in an oven at 80 °C and dry it for 30 h to completely dry and remove binder. Then, perform isostatic pressing at 200 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0069] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1400°C for 4 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0070] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0071] The ceramic resistor prepared in Example 2 has the following performance indicators after sampling inspection: volume density is 2.30 g / cm 3 , compressive strength is 201 MPa, resistance value is 4.85 Ω, temperature resistance coefficient is -0.042% / ℃, voltage coefficient is -1.39%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0072] Example 3 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 40 °C on a water bath heating magnetic stirrer at a speed of 1250 r / min for 80 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0073] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1250 r / min and 40°C for 80 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0074] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35°C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55°C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0075] S4. Place the impregnated porous mullite in an electric hot air dryer at 80°C for 20 hours until it is completely dry.
[0076] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 83 μm are obtained.
[0077] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0078] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1.5% of polyvinyl alcohol and 1.5% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 64% of bauxite, 8% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0079] S7. Place the ceramic slurry in an oven at 80 °C and dry it for 30 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0080] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1400°C for 4 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0081] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0082] The ceramic resistor prepared in Example 3 was sampled and inspected, and the performance indicators were as follows: the volume density was 2.31 g / cm 3 , compressive strength is 193 MPa, resistance value is 4.87 Ω, temperature resistance coefficient is -0.045% / ℃, voltage coefficient is -1.76%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0083] Example 4 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 60 ° C for 100 min at a speed of 1350 r / min on a water bath heating magnetic stirrer until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0084] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1350 r / min and 60 °C for 100 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0085] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35°C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55°C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0086] S4. Place the impregnated porous mullite in an electric hot air dryer at 80°C for 20 hours until it is completely dry.
[0087] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 83 μm are obtained.
[0088] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0089] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1.5% of polyvinyl alcohol and 1.5% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 64% of bauxite, 8% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0090] S7. Place the ceramic slurry in an oven at 80 °C and dry it for 30 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0091] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1400°C for 4 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0092] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0093] The ceramic resistor prepared in Example 4 was sampled and inspected, and the performance indicators were as follows: the volume density was 2.32 g / cm 3 The compressive strength is 218 MPa, the resistance value is 4.89 Ω, the temperature resistance coefficient is -0.037% / ℃, and the voltage coefficient is -1.43%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0094] Example 5 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 40 °C on a water bath heating magnetic stirrer at a speed of 1250 r / min for 80 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0095] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1250 r / min and 40°C for 80 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0096] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35°C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55°C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0097] S4. Place the impregnated porous mullite in an electric hot air dryer at 60°C for 36 hours until it is completely dry.
[0098] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 1000℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and the carbon-ceramic composite conductive microspheres with a diameter of 80 μm are obtained.
[0099] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0100] S6. In terms of mass percentage, 1 part of ceramic raw material, 8% of carbon-ceramic composite conductive microspheres, 1% of polyvinyl alcohol and 1% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 63% of bauxite, 8% of silicon powder, 17% of kaolin and 12% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of the ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 600 rpm, the impregnation time is 6 h, and the ceramic slurry is obtained by mixing.
[0101] S7. Place the ceramic slurry in a 60°C oven and dry it for 36 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0102] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1300°C for 2 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0103] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0104] The ceramic resistor prepared in Example 5 has the following performance indicators after sampling inspection: volume density is 2.26 g / cm 3 , compressive strength is 166 MPa, resistance value is 5.08 Ω, temperature resistance coefficient is -0.066% / ℃, voltage coefficient is -1.34%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0105] Example 6 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 40 °C on a water bath heating magnetic stirrer at a speed of 1250 r / min for 80 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0106] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1250 r / min and 40°C for 80 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0107] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35°C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55°C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0108] S4. Place the impregnated porous mullite in an electric hot air dryer at 60°C for 36 hours until it is completely dry.
[0109] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 3 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 90 μm are obtained.
[0110] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0111] S6. In terms of mass percentage, 1 part of ceramic raw material, 5% of carbon-ceramic composite conductive microspheres, 0.5% of polyvinyl alcohol and 0.5% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 67% of bauxite, 6% of silicon powder, 19% of kaolin and 8% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw materials and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 300 rpm, the impregnation time is 2 h, and the ceramic slurry is obtained by mixing.
[0112] S7. Place the ceramic slurry in a 100 °C oven and dry it for 18 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0113] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1300°C for 3 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0114] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0115] The ceramic resistor prepared in Example 6 has the following performance indicators after sampling inspection: volume density is 2.28 g / cm 3 , compressive strength is 174 MPa, resistance value is 4.92 Ω, temperature resistance coefficient is -0.034% / ℃, voltage coefficient is -0.82%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0116] Example 7 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 40 °C on a water bath heating magnetic stirrer at a speed of 1250 r / min for 80 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0117] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1250 r / min and 40°C for 80 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0118] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35°C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55°C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0119] S4. Place the impregnated porous mullite in an electric hot air dryer at 60°C for 36 hours until it is completely dry.
[0120] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 900℃ for 4 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and the carbon-ceramic composite conductive microspheres with a diameter of 82 μm are obtained.
[0121] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0122] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1% of polyvinyl alcohol and 1% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 65% of bauxite, 7% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0123] S7. Place the ceramic slurry in an oven at 80 °C and dry it for 30 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0124] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1350°C for 3 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0125] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0126] The ceramic resistor prepared in Example 7 was sampled and inspected, and the performance indicators were as follows: the volume density was 2.29 g / cm 3 , compressive strength is 181 MPa, resistance value is 4.90 Ω, temperature resistance coefficient is -0.052% / ℃, voltage coefficient is -1.81%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0127] Example 8 A method for preparing carbon ceramic composite conductive microspheres comprises the following steps: S1. Weigh 1.5% of ammonium cobalt acetate by mass percentage and place it in 55% tartaric acid solution, and mix and react at 40 °C on a water bath heating magnetic stirrer at a speed of 1250 r / min for 80 min until the ammonium cobalt acetate and the tartaric acid solution are evenly mixed to obtain a carbon precursor solution.
[0128] S2. In terms of mass percentage, 1.5% of octylphenol polyoxyethylene ether was weighed and placed in 18% of carbon black solution, and the mixture was stirred on a water bath heating magnetic stirrer at a speed of 1250 r / min and 40°C for 80 min until the mixture was uniformly stirred to obtain a carbon black slurry.
[0129] S3. By mass percentage, 30% of porous mullite is placed in a vacuum barrel. The apparent porosity of the porous mullite is 45%. The vacuum pump is turned on to remove the gas in the barrel. When the pressure indication is stable at -0.098 MPa, the valve switch connected to the precursor solution is slowly opened. The carbon precursor solution is first completely injected into the vacuum barrel, and the valve switch is closed. The first impregnation is carried out and the impregnation is maintained at 35 °C for 2 hours. Then the carbon black slurry is injected for the second impregnation and the impregnation is continued at 55 °C for 2 hours. Ensure that the porous mullite is fully infiltrated. After the impregnation, the vacuum pump is turned off and the sample is taken out.
[0130] S4. Place the impregnated porous mullite in an electric hot air dryer at 60°C for 36 hours until it is completely dry.
[0131] S5. The porous mullite powder after impregnation and drying treatment is formed into a φ35 mm×30 mm cylindrical sample at 4 MPa and placed in a graphite crucible, then buried in a corundum-mullite crucible, and coke is filled in the gap between the graphite crucible and the corundum-mullite crucible. Finally, the corundum-mullite crucible is placed in a high-temperature furnace and kept at 800℃ for 5 h for carbon sintering to ensure that tartaric acid is completely pyrolyzed and carbonized into carbon material. After the insulation is completed, the sample is cooled to room temperature with the furnace, and then the carbon-ceramic composite conductive microspheres with a diameter of 83 μm are obtained.
[0132] A method for preparing a ceramic resistor comprises the following steps: Step S1 to step S5 are the same as the preparation method of carbon ceramic composite conductive microspheres, with carbon ceramic composite conductive microspheres being used as conductive fillers.
[0133] S6. In terms of mass percentage, 1 part of ceramic raw material, 9% of carbon-ceramic composite conductive microspheres, 1% of polyvinyl alcohol and 1% of lecithin are added to deionized water. In terms of mass percentage, the ceramic raw material includes 65% of bauxite, 7% of silicon powder, 18% of kaolin and 10% of raw clay. The slurry consisting of carbon-ceramic composite conductive microspheres and polyvinyl alcohol is impregnated into the mud consisting of ceramic raw material and lecithin in a manipulator single-cylinder impregnation and spinning coating machine by vacuum-assisted centrifugal impregnation. The vacuum degree of vacuum-assisted centrifugal impregnation is controlled to be maintained at 0.3 atm, the rotation speed is 400 rpm, the impregnation time is 3 h, and the ceramic slurry is obtained by mixing.
[0134] S7. Place the ceramic slurry in a 60°C oven and dry it for 36 h to completely dry and remove binder. Then, perform isostatic pressing at 260 MPa in a dry belt cold isostatic press to obtain a ceramic green body.
[0135] S8. Place the ceramic green body in an inert atmosphere for gas pressure sintering at a sintering temperature of 1350°C for 4 hours. After the insulation is completed, cool the green body to room temperature with the furnace, take out the green body, and obtain a ceramic resistor green body.
[0136] S9, subjecting the ceramic resistor body to mechanical processing and spraying electrodes to obtain a ceramic resistor.
[0137] The ceramic resistor prepared in Example 8 has the following performance indicators after sampling inspection: volume density is 2.29 g / cm 3 , compressive strength is 186 MPa, resistance value is 4.98 Ω, temperature resistance coefficient is -0.055% / ℃, voltage coefficient is -1.98%cm / kV. It meets the performance requirements of the industry standard for new carbon ceramic closing resistors.
[0138] Comparative Example 1 The difference from Example 1 is that in step S3, the time of the first immersion is 10 min, the time of the second immersion is 10 min, and in step S6, the immersion time of the vacuum-assisted centrifugal immersion is 20 min.
[0139] The ceramic resistor prepared in Comparative Example 1 was sampled and inspected, and the performance indicators were as follows: the volume density was 1.72 g / cm 3 , the compressive strength is 105 MPa, the resistance value is 10.82 Ω, and the resistivity deviation is large, the temperature resistivity is -0.018% / ℃, and the voltage coefficient is -3.2% cm / kV. By comparison, the mechanical properties and electrical properties of the ceramic resistor prepared in Comparative Example 1 are much lower than those of the ceramic resistor prepared in Example 1. The ceramic resistor prepared by the present invention has excellent mechanical properties, low and more stable resistivity, high mechanical strength, and can effectively ensure the safe operation of the product.
[0140] Comparative Example 2 The difference from Example 1 is that in step S6, the amount of carbon ceramic composite conductive microspheres added to the ceramic raw material is 3% by mass.
[0141] The ceramic resistor prepared in Comparative Example 2 was sampled and inspected, and the performance indicators were as follows: the volume density was 2.39 g / cm 3 , compressive strength is 199 MPa, resistance value is 10.37 Ω, temperature resistance coefficient is -0.014% / ℃, and voltage coefficient is -2.7%cm / kV. By comparison, the mechanical properties and electrical properties of the ceramic resistor prepared in Comparative Example 2 are much lower than those of the ceramic resistor prepared in Example 1. The ceramic resistor prepared by the present invention has excellent mechanical properties, low and more stable resistivity, high mechanical strength, and can effectively ensure the safe operation of the product.
[0142] Comparative Example 3 The difference from Example 1 is that in step S8, the sintering temperature is 1200°C.
[0143] The ceramic resistor prepared in Comparative Example 3 was sampled and inspected, and the performance indicators were as follows: the volume density was 2.01 g / cm 3 , compressive strength is 133 MPa, and resistance is 8.96 Ω. The temperature resistance coefficient is -0.021% / ℃, and the voltage coefficient is -0.96% cm / kV. By comparison, the mechanical properties and electrical properties of the ceramic resistor prepared in Comparative Example 3 are much lower than those of the ceramic resistor prepared in Example 1. The ceramic resistor prepared by the present invention has excellent mechanical properties, low and more stable resistivity, high mechanical strength, and can effectively ensure the safe operation of the product.
[0144] Table 1 Comparison of performance indicators of ceramic resistors prepared in Examples 1-8 and Comparative Examples 1-3
[0145] Table 1 is a comparison of the performance indicators of the ceramic resistors prepared in Examples 1-8 and Comparative Examples 1-3; it can be seen from the table that the ceramic resistors prepared in Examples 1-8 disclosed in the present invention, after sampling inspection, all meet the performance requirements of the industry standard for new carbon ceramic switching resistors, that is, the volume density is ≥2.25 g / cm 3 , compressive strength ≥ 120 MPa, resistance value 5 ± 0.25 Ω, temperature resistance coefficient of -0.05 ~ 0.1% / ° C, voltage coefficient of -7.5 ~ -0.5% cm / kV. The mechanical properties and electrical properties of the ceramic resistors prepared in Comparative Examples 1-3 are much lower than those of the ceramic resistors prepared in Examples 1-8 of the present invention. The ceramic resistors prepared by the present invention have excellent mechanical properties, low and more stable resistivity, high mechanical strength, and can effectively ensure the safe operation of the product.
[0146] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing carbon ceramic composite conductive microspheres, characterized in that: include: The ceramic phase matrix is firstly impregnated in a carbon precursor solution, then impregnated in a carbon black slurry for a second time, and then dried and carbon-embedded and sintered in sequence to obtain carbon-ceramic composite conductive microspheres; The carbon precursor solution is prepared by adding ammonium cobalt acetate to a tartaric acid solution and mixing them for reaction; The carbon black slurry is prepared by adding octylphenol polyoxyethylene ether to a carbon black solution and stirring the mixture for reaction; The ceramic phase matrix is porous mullite.
2. The method for preparing carbon ceramic composite conductive microspheres according to claim 1, characterized in that: The mass percentages of the ammonium cobalt acetate, tartaric acid solution, octylphenol polyoxyethylene ether, carbon black solution and porous mullite are (1%-2%): (50%-60%): (1%-2%): (15%-20%): (20%-35%); the apparent porosity of the porous mullite is 30%-60%.
3. The method for preparing carbon ceramic composite conductive microspheres according to claim 1, characterized in that: The temperature of the first impregnation is 40-60°C, and the time of the first impregnation is 1-4 h; the temperature of the second impregnation is 40-60°C, and the time of the second impregnation is 1-4 h; the first impregnation and the second impregnation are both carried out in a vacuum environment, and the pressure is maintained at -0.098 MPa; The mixing reaction conditions are: mixing reaction at a speed of 1100-1350 r / min, at 30-60°C for 40-100 min; The stirring reaction conditions are: stirring the reaction at a speed of 1100-1350 r / min and at 30-60° C. for 40-100 min; The drying temperature is 60-100°C and the drying time is 18-36 hours.
4. The method for preparing carbon ceramic composite conductive microspheres according to claim 1, characterized in that: The temperature of the carbon-embedded sintering is 800-1000° C., and the insulation time of the carbon-embedded sintering is 3-5 h.
5. A carbon ceramic composite conductive microsphere, characterized in that: The carbon-ceramic composite conductive microspheres are prepared by the preparation method of any one of claims 1 to 4, wherein the carbon-ceramic composite conductive microspheres include ceramic phase porous mullite and conductive phase carbon contained inside the ceramic phase porous mullite; the diameter of the carbon-ceramic composite conductive microspheres is 80-90 μm.
6. A method for preparing a ceramic resistor, characterized in that: The following steps are involved: The slurry composed of the conductive filler and the binder is impregnated in the mud composed of the ceramic raw material and the surfactant by vacuum-assisted centrifugal impregnation, and then dried and debinded, isostatically pressed and sintered by gas pressure are performed in sequence, cooled to room temperature, and then mechanically treated and sprayed with electrodes to obtain a ceramic resistor; The conductive filler is a carbon ceramic composite conductive microsphere prepared by the preparation method of carbon ceramic composite conductive microspheres according to any one of claims 1 to 4.
7. The method for preparing a ceramic resistor according to claim 6, characterized in that: The mass percentages of the conductive filler, binder, ceramic raw material and surfactant are (5%-9%): (0.5%-1.5%): 1: (0.5%-1.5%); Wherein, in terms of mass percentage, the ceramic raw material comprises 63%-67% of bauxite, 6%-8% of silica powder, 17%-19% of kaolin and 8%-12% of raw clay; The binder is polyvinyl alcohol; The surfactant is lecithin.
8. The method for preparing a ceramic resistor according to claim 6, characterized in that: The vacuum degree of the vacuum-assisted centrifugal impregnation method is maintained at 0.3 atm, the rotation speed is 300-600 rpm, and the impregnation time is 2-6 h; The drying temperature is 60-100°C and the drying time is 18-36 hours.
9. The method for preparing a ceramic resistor according to claim 6, characterized in that: The pressure of the primary isostatic pressing is 200-300 MPa; The sintering temperature of the gas pressure sintering is 1300-1400°C, and the holding time is 2-4 h.
10. A ceramic resistor, characterized in that: The ceramic resistor is prepared by the preparation method of any one of claims 6 to 9, wherein the volume density of the ceramic resistor is ≥ 2.25 g / cm 3 .
Citation Information
Patent Citations
Copper-based nano catalyst for preparing high-carbon alcohol from synthetic gas as well as preparation method and application thereof
CN102500374A
Flexible loading type carbon fiber loaded CoB catalyst and preparation method thereof
CN105107509A
Cited By
Carbon ceramic composite conductive microsphere, ceramic resistor and preparation method
CN120496949A
Carbon brick, preparation method thereof and graphitization furnace
CN120535330A
C / SiC-ZrB2-HfB2-Cu composite material and preparation method thereof
CN122102699A